(untitled) (Ozone Therapy Global Journal, 2022)
Spondylodiscitis (SD) is a condition of generally infectious etiology that compromises the vertebral body and adjacent intervertebral discs, produces moderate to severe pain and is disabling. There are few papers of the application of ozone therapy in SD. The objective of this report is to present and discuss the case of a patient diagnosed with SD treated with ozone therapy as an adjunct to antibiotic therapy. A 51-year-old man who, after beginning with urinary sepsis, was diagnosed with type II diabetes mellitus. Subsequently, he presented cystitis and prostatitis. Urine culture was positive for Staphylococcus aureus; he was treated with antibiotics. Twenty-five days later, he presented dysuria, associated with lower back pain, with no history of trauma. He was treated with anti-inflammatories and analgesics, without improvement. A magnetic resonance imaging was performed with an image suggestive of spondylodiscitis at level L4-L5. He was hospitalized, treated with tramadol and vancomycin without improvement. Nine days after starting antibiotic therapy, treatment with ozone therapy was added, performing intradiscal and paravertebral infiltrations with ozone. Twenty-four days after starting treatment with ozone therapy, the patient eliminated the infection, the pain decreased on the visual analog scale from 10 to 2. There were no adverse effects. Patient was discharged. He returned home and began to do activities of daily living, without the need of analgesics or anti-inflammatories. He did not present sequelae of the disease. The application of intradiscal and paravertebral ozone, as a coadjuvant therapy associated with antibiotic therapy, seems to be an option in the treatment of spondylodiscitis. Further studies with a larger number of cases are required to prove it..